The professionalization of humanitarian organizations : the art of balancing multiple stakeholder interests at the ICRC /: the art of balancing multiple stakeholder interests at the ICRC. ([2019]) - Müller-Stewens, Günter; Dinh, Tami; Hartmann, Bettina; Eppler, Martin J, 1971-; Bünzli, Fabienne
No abstract available